2019
DOI: 10.4103/1735-5362.268206
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity assay of D-limonene niosomes: an efficient nano-carrier for enhancing solubility of plant-extracted agents

Abstract: The low solubility of the plant-extracted agent like D-limonene in cancer therapy is a critical problem. In this study, we prepared D-limonene-loaded niosomes (D-limonene/Nio) for cancer therapy through in vitro cytotoxicity assay of HepG2, MCF-7, and A549 cell lines. The niosomal formulation was prepared by film hydration technique with Span® 40: Tween® 40: cholesterol (35:35:30 molar ratio) and characterized for vesicle distribution size, morphology, entrapment efficiency (EE%), and in vitro release behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…The loading of limonene into SLNs decreased cell viability down to 76.27 ± 1.63% (10 µg/mL, at 48 h incubation), while remaining above 70%, which is required to confirm the non-cytotoxic profile. Compared with previous studies [26], in which tumoral cell lines were used, in this study ( Figure 3) the growth inhibition was below 30%, which may indicate a low toxic effect to the non-tumoral cell line HaCaT. The selective effect of (+)-limonene 1,2-epoxide is of interest in several areas of knowledge, deserving further deeper study.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…The loading of limonene into SLNs decreased cell viability down to 76.27 ± 1.63% (10 µg/mL, at 48 h incubation), while remaining above 70%, which is required to confirm the non-cytotoxic profile. Compared with previous studies [26], in which tumoral cell lines were used, in this study ( Figure 3) the growth inhibition was below 30%, which may indicate a low toxic effect to the non-tumoral cell line HaCaT. The selective effect of (+)-limonene 1,2-epoxide is of interest in several areas of knowledge, deserving further deeper study.…”
Section: Resultscontrasting
confidence: 62%
“…By plotting the obtained results, a linear regression (y = 4.2026x − 2.644) of R 2 = 0.9902 was obtained and the IC 50 calculated as 207.5 µg/mL. Previous studies have demonstrated the cytotoxicity and anti-tumor activity of (+)-limonene 1,2-epoxide in different cell lines (OVCAR-8, HCT-116, and SF-295), with percentages of growth inhibition varying between 58.48% (SF-295 cells) and 93.10% (OVCAR-8 cells) [26]. We anticipated that the loading of limonene into SLNs could reduce the cytotoxic effect in cells while keeping the antioxidant activity, as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The activity is most likely a synergistic effect among the major monoterpenes found in the A. polystachya essential oil [37]. Among the identified terpenes, D-limonene has a demonstrated ability to inhibit cell proliferation, e.g., by inducing apoptosis in lung, stomach, and gastric liver cells [38]. Furthermore, carvone has been shown to be cytotoxic in some tumor cell lines [39,40]; for example, M. spicata oil-with similar carvone content (65.33%)-showed similar cytotoxic activity against the HeLa cell line [41], with IC 50 values below 10 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…At low concentrations, it resulted in production of H 2 O 2 and ERK pathway activation, while at high concentrations it inhibited the farnesylation of proteins and O 2 production [179]. Niosomes containing D-limonene (20 µM) exerted cytotoxic effects on HepG2 and other cell lines [168]. The combination of D-limonene and docetaxel improved the cytotoxicity to DU-145 human prostate carcinoma cells compared to docetaxel alone.…”
Section: Limonenementioning
confidence: 99%